Making Sense of the Seascape - Jan Paul Crielaard (Cahiers Mondes Anciens)
This paper is based on the notion that the sea is a knowable, textured place that through senses, observations, skill, myths and narratives can be described and mapped. Anthropological research shows that stories and myths are crucial to give meaning to and make sense of the seascape. In ancient Greece, this type of information formed keystones in building narrative maps that could be passed on verbally to seafarers, including those who had not visited the area before. In this paper I intend to show that ancient Greek stories and myths connected to seas and coasts contained spatial information and elements of cognitive mapping that could have served practical purposes when it came to spatial orientation and wayfinding across the seascape.